Pengaruh Terapi Relaksasi Autogenik Terhadap Kecemasan dan Nyeri Pasien Diruang Intensive Care Unit (ICU) : Literature Review - Tiara Yulita Utami; Slamet Purnomo (Universitas Duta Bangsa Surakarta, 2021)
Introduction: Undergoing care in the ICU room can cause stressors for patients and families. Stressors that appearcan consist of physical stressors, the environment is also psychological. The factors that influence the incidence in ICUpatients discussed earlier, pain, difficulty, environment and difficulty. Relaxation is mental and physical freedomfrom rest and stress. Relaxation techniques provide self-control to individuals who feel uncomfortable, physical andemotional stress when sick. Relaxation techniques can be used when individuals are in a healthy or sick condition.Objectives: To identification, analysis and evaluation autogenic relaxation therapy on anxiety and pain in ICUpatients.Methods: This research uses a systematic literature review (SLR), with search method using Google scholar, PubMedand Science direct.Results: Based on the results of the analysis, there were 10 research articles and there was a significant effect ofautogenic relaxation therapy on patient anxiety and pain in the intensive care unit (ICU).Conclusions: There is a significant effect of autogenic relaxation therapy on the anxiety of patients being treated inthe ICU and there are some who explain that autogenic relaxation affects pain and blood pressure.